The Effect of Problem-based Learning with Reading Questioning Answering Strategy on Students’ Metacognitive Skills of Acid Base Concept - Ghiska Primayana Mufhtih; Dedi Irwandi; Evi Sapinatul Bahriah (Pendidikan Kimia Unimus, 2021)
Metacognitive skills are one of the skills needed in the 21st century to achieve student learning success. Student’s metacognitive skills are still low, so that need to be empowered during the learning process by implementing Problem Based Learning Strategy Integrated with Reading Questioning Answering (PBLRQA). Through the PBLRQA strategy, students can control their cognitive processes by planning, monitoring, and evaluating to solve problems in chemistry learning. The aim of this research was to determine the effectiveness of the PBLRQA strategy on students’ metacognitive skills on acid-base materials. The method was used quasi-experiment with a non-equivalent control group design. The sample in this study were students of class XI IPA 1 as the experimental group and students of class XI IPA 5 as the control group, with each class including 32 students. Instruments Metacognitive Activities Inventory (MCA-I) developed by Cooper and Sandi-Urena (2009) were used in this research. Data analysis was assisted by IBM SPSS Statistic 22 software. The results of this research indicated that the use of PBLRQA strategy on acid-base materials was able to empowering students’ metacognitive skills.